Low-temperature plasmas in carbon nanostructure synthesis - Levchenko, Igor; Keidar, Michael; Xu, Shuyan; Kersten, Holger; Ostrikov, Kostya (Ken) (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2013)
Plasma-based techniques offer many unique possibilities for the synthesis of various nanostructures both on the surface and in the plasma bulk. In contrast to the conventional chemical vapor deposition and some other techniques, plasma-based processes ensure high level of controllability, good quality of the produced nanomaterials, and reduced environmental risk. In this work, the authors briefly review the unique features of the plasma-enhanced chemical vapor deposition approaches, namely, the techniques based on inductively coupled, microwave, and arc discharges. Specifically, the authors consider the plasmas with the ion/electron density ranging from 1010 to 1014 cm−3, electron energy in the discharge up to ∼10 eV, and the operating pressure ranging from 1 to 104 Pa (up to 105 Pa for the atmospheric-pressure arc discharges). The operating frequencies of the discharges considered range from 460 kHz for the inductively coupled plasmas, and up to 2.45 GHz for the microwave plasmas. The features of the direct-current arc discharges are also examined. The authors also discuss the principles of operation of these systems, as well as the effects of the key plasma parameters on the conditions of nucleation and growth of the carbon nanostructures, mainly carbon nanotubes and graphene. Advantages and disadvantages of these plasma systems are considered. Future trends in the development of these plasma-based systems are also discussed.